Metode PQ4R dalam Kemampuan Pemahaman Membaca Siswa Sekolah Dasar: Systematic Literature Review (SLR) - Firly Istiqomah; Dase Erwin Juansah (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Reading comprehension is a very important skill in our learning and in our lives. With this reading comprehension ability, one can also obtain information more effectively, develop knowledge, and understand other people's perspectives and experiences that can enrich their thinking and worldview. And the PQ4R method is a solution to the problem of the lack of reading comprehension skills, the steps are Preview, Question, Read, Reflect, Recite, and Review. The purpose of this research is to conduct a literature review related to the PQ4R method and also its effect on reading comprehension skills in elementary school students. In this study, researchers used the SLR (Systematic Literature Review) method. All research articles that have conducted similar research are included in the research report to obtain data. The research journal articles utilized in this study were 21 national journal articles and 1 international article. The articles were obtained from the Google Scholar database with the help of the Publish or Perish application. The research results from several journal articles that have been reviewed, according to many studies analyzed about the use of the PQ4R method, the PQ4R method can improve reading comprehension, and can also improve student learning outcomes in elementary schools. On analyzing the results of several studies, the PQ4R method is not only used to improve reading comprehension skills but can also be used in other subject matter.